Heidi A. Campbell & Ruth Tsuria (Eds.), â€œDigital Religion: Understanding Religious Practice in Digital Media (2nd edition)â€, Routledge, 2022. ISBN 978-0-367-25775-7 - Yildiz Sumeyye (LP2M Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2022)
Digital religion, or issues on religion and digital media, are the expertise of Heidi A. Campbell and Ruth Tsuria. Both are prominent scholars on this topic, and this edited book is one of their latest important works. The review will describe the book entitled â€œDigital Religion: Understanding Religious Practice in Digital Mediaâ€ edited by Heidi A. Campbell and Ruth Tsuria. This study developed because of the presence of social media that gave rise to digital cultural arenas such as virtual reality, artificial intelligence, the internet of things, and big data. From here, the digital religion field develops in various ways. In this book review, several notes can be shared to be used as an assessment before reading. This book highlights the dynamics of such research in a variety of topics whose questions come from artificial intelligence and the influence of technological views.